Development and Content Validity of the Bilateral Vestibulopathy Questionnaire - van Stiphout, Lisa; Hossein, Israt; Kimman, Merel; Whitney, Susan L.; Ayiotis, Andrianna; Strupp, Michael; Guinand, Nils; Pérez Fornos, Angélica; Widdershoven, Josine; Ramos-Macías, Ángel; Van Rompaey, Vincent; van de Berg, Raymond (Frontiers in Neurology, 2022)
Objective:To date, the burden and severity of the full spectrum of bilateral vestibulopathy (BVP) symptoms has not yet been measured in a standardized manner. Since therapeutic interventions aiming to improve BVP symptoms are emerging, the need for a new standardized assessment tool that encompasses the specific aspects of BVP arises. Therefore, the aim of this study was to develop a multi-item Patient Reported Outcome Measure (PROM) that captures the clinically important symptoms of BVP and assesses its impact on daily life. Methods:The development of the Bilateral Vestibulopathy Questionnaire (BVQ) consisted of two phases: (I) initial item generation and (II) face and content validity testing. Items were derived from a literature review and individual semi-structured interviews focusing on the full spectrum of reported BVP symptoms (I). Subsequently (IIa), individual patient interviews were conducted using “thinking aloud” and concurrent verbal probing techniques to assess the comprehensibility of the instructions, questions and response options, and the relevance, missing domains, or missing items. Interviews continued until saturation of input was reached. Finally, international experts with experience in the field of the physical, emotional, and cognitive symptoms of BVP participated in an online focus group to assess the relevance and comprehensiveness of the BVQ (IIb). Results:The BVQ consisted of two sections. The first section included 50 items scored on a six-point Likert scale arranged into seven constructs (i.e., imbalance, oscillopsia, other physical symptoms, cognitive symptoms, emotional symptoms, limitations and behavioral changes and social life). The second section consisted of four items, scored on a visual analog scale from 0 to 100, to inquire about limitations in daily life, perceived health and expectations regarding future recovery. Interviews with BVP patients [n=8, 50% female, mean age 56 years (range 24-88 years)] and the expert meeting confirmed face and content validity of the developed BVQ. Conclusion:The BVQ, which was developed to assess the spectrum of BVP symptoms and its impact on daily life, proved to have good face and content validity. It can be used to characterize current self-reported symptoms and disability and to evaluate symptom burden before and after therapeutic interventions in future research and clinical practice.